Protective potential of Vitamin E against methylphenidate-induced male gonadal changes in albino rats - Iqbal, Sadia (Int J Health Sci (Qassim), 2019)
OBJECTIVE: Attention deficit hyperactivity disorder ranks among the top neuropsychiatric disorder of childhood and adolescents. Methylphenidate (MPH) is the most frequently used pharmacologic agent to treat this condition. Its long-term use has been associated with many unwanted and adverse effects on many organs including male gonads, but so far no study has been done to find out a protective agent. This study investigated the protective potential of Vitamin E (Vit E) against the microscopic and morphometric alterations in male gonads induced by MPH, using albino rats. METHODS: Adult male albino rats were assigned into three equal groups including one control and two experimental groups. Experimental groups administered with MPH (10 mg/kg) and MPH (10 mg/kg) + Vit E orally (50 mg/kg), daily for 40 days. Testes of the sacrificed animals were removed, processed, and stained with hematoxylin and eosin for examining the microscopic and morphometric alterations and protective potential of Vit E. Data were analyzed using ANOVA. RESULTS: Experimental animals treated with MPH showed a significant decrease in the diameter of seminiferous tubules (296.86 ± 14.70 µm) and height of germinal epithelium (51.73 ± 3.15 µm) with a corresponding gain in the thickness of the interstitium (47.05 ± 4.94 µm). Animals treated with MPH + Vit E did not reveal any significant testicular microscopic changes and seminiferous tubular alterations induced by MPH. CONCLUSION: Vit E demonstrated a protective potential against the adverse changes induced by MPH in the male gonads in albino rats.